Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a)x4+5x3+10x-4
=x4+2x2+5x3+10x-2x2-4
=x2(x2+2)+5x(x2+2)-2(x2+2)
=(x2+5x-2)(x2+2)
b)x3+y3+z3-3xyz
= (x+y)³ - 3xy(x-y) + z³ - 3xyz
= [(x+y)³ + z³] - 3xy(x+y+z)
= (x+y+z)³ - 3z(x+y)(x+y+z) - 3xy(x-y-z)
= (x+y+z)[(x+y+z)² - 3z(x+y) - 3xy]
= (x+y+z)(x² + y² + z² + 2xy + 2xz + 2yz - 3xz - 3yz - 3xy)
= (x+y+z)(x² + y² + z² - xy - xz - yz).
![](https://rs.olm.vn/images/avt/0.png?1311)
A= x4 + 64
A= (x2)2 + 2.x2.8 +82 - (2.x2 .8)
A=(x2+8)2 -16x2
A =(x2+8+4x).(x2+8-4x)
-
G=(x2+y2+z2)2 (có sẵn hdt rồi mak_)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/
\(=x^2\left(x^2+2x+1\right)=x^2\left(x+1\right)^2\)
b/
\(=x^3+3x^2y+3xy^2+y^3-\left(x+y\right)\)
\(=\left(x+y\right)^3-\left(x+y\right)\)
\(=\left(x+y\right)\left[\left(x+y\right)^2-1\right]\)
\(=\left(x+y\right)\left(x+y+1\right)\left(x+y-1\right)\)
c/
Đề sai, câu này ko phân tích được
d/
\(=a^3\left(a^2+1\right)-\left(a^2+1\right)\)
\(=\left(a^3-1\right)\left(a^2+1\right)\)
\(=\left(a-1\right)\left(a^2+1\right)\left(a^2+a+1\right)\)
e.
\(=x^4+4x^2+4-4x^2\)
\(=\left(x^2+2\right)^2-\left(2x\right)^2\)
\(=\left(x^2-2x+2\right)\left(x^2+2x+2\right)\)
f.
\(=4x^4+4x^2y^2+y^4-4x^2y^2\)
\(=\left(2x^2+y^2\right)^2-\left(2xy\right)^2\)
\(=\left(2x^2-2xy+y^2\right)\left(2x^2+2xy+y^2\right)\)
g.
\(=81x^4+36x^2+4-36x^2\)
\(=\left(9x^2+2\right)^2-\left(6x\right)^2\)
\(=\left(9x^2-6x+2\right)\left(9x^2+6x+2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 7x^3 + 5 ( x - y )^2 v- 7y^3
= 7 ( x^3 - y^3 ) + 5 ( x-y )^2
= 7 ( x - y )^3 + 5 ( x-y ) ^2
= [ 7 ( x- y ) + 5 ] ( x-y) ^2
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a: \(6x^2-11x+3\)
\(=6x^2-9x-2x+3\)
\(=3x\left(2x-3\right)-\left(2x-3\right)\)
\(=\left(2x-3\right)\left(3x-1\right)\)
b: \(2x^2+3x-27\)
\(=2x^2+9x-6x-27\)
\(=x\left(2x+9\right)-3\left(2x+9\right)\)
\(=\left(2x+9\right)\left(x-3\right)\)
c: \(x^2-10x+24\)
\(=x^2-4x-6x+24\)
\(=x\left(x-4\right)-6\left(x-4\right)\)
\(=\left(x-4\right)\left(x-6\right)\)
d: \(49x^2+28x-5\)
\(=49x^2+28x+4-9\)
\(=\left(7x+2\right)^2-9\)
\(=\left(7x-1\right)\left(7x+5\right)\)
e: \(2x^2-5xy-3y^2\)
\(=2x^2-6xy+xy-3y^2\)
\(=2x\left(x-3y\right)+y\left(x-3y\right)\)
\(=\left(x-3y\right)\left(2x+y\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(2x^2+3x-5=2x^2-2x+5x-5\)
\(=2x\left(x-1\right)+5\left(x-1\right)=\left(x-1\right)\left(2x+5\right)\)
b) \(\left(x+y+z\right)^3-x^3-y^3-z^3\)
\(=\left(x+y\right)^3+3z\left(x+y\right)\left(x+y+z\right)+z^3-x^3-y^3-z^3\)
\(=x^3+y^3+z^3+3xy\left(x+y\right)+3z\left(x+y\right)\left(x+y+z\right)-x^3-y^3-z^3\)
\(=3\left(x+y\right)\left[xy+z\left(x+y+z\right)\right]\)
\(=3\left(x+y\right)\left(xy+xz+yz+z^2\right)\)
\(=3\left(x+y\right)\left(y+z\right)\left(z+x\right)\)
c) \(x^4+x^3+x+1=x^3\left(x+1\right)+\left(x+1\right)=\left(x+1\right)\left(x^3+1\right)=\left(x+1\right)^2\left(x^2-x+1\right)\)
d) \(x^4-x^3-x^2+1=x^2\left(x-1\right)-\left(x-1\right)\left(x+1\right)=\left(x-1\right)\left(x^2-x-1\right)\)
e) \(x^4+4x^2-5=\left(x^2+2\right)^2-9=\left(x^2+2+3\right)\left(x^2+2-3\right)=\left(x^2+5\right)\left(x+1\right)\left(x-1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 10x(x - y)2 - 5(x - y)3 = [10x - 5(x - y)](x - y)2 = (10x - 5x + y)(x - y)2 = (5x + y)(x - y)2
b) -x2 - 10x - 25 = -(x2 + 10x + 52) = -(x + 5)2
c) 64x6y4 - 81x2y2 = (8x3y2)2 - (9xy)2 = (8x3y2 + 9xy)(8x3y2 - 9xy)
d) x6 - y6 = (x3)2 - (y3)2 = (x3 - y3)(x3 + y3) = (x - y)(x2 + xy + y2)(x + y)(x2 - xy + y2)
e)1/8x3 - 3/4x2y + 3/2xy2 - y3 = (1/2x)3 - 3.(1/2x)2y + 3.1/2xy2 - y3 = (1/2x - y)3
f) (3x + 1)2 - (x - 1)2 = (3x + 1 + x - 1)(3x + 1 - x + 1) = 4x(2x + 2) = 8x(x + 1)
b: \(x^3+y^3+z^3-3xyz\)
\(=\left(x+y\right)^3+z^3-3xy\left(x+y\right)-3xyz\)
\(=\left(x+y+z\right)\left(x^2+2xy+y^2-xz-yz+z^2\right)-3xy\left(x+y+z\right)\)
\(=\left(x+y+z\right)\left(x^2+y^2+z^2-xy-xz-yz\right)\)
c: \(x^7+x^2+1\)
\(=x^7+x^6+x^5-x^6-x^5-x^4+x^4+x^3+x^2-x^3+1\)
\(=\left(x^2+x+1\right)\left(x^5-x^4+x^2\right)-\left(x-1\right)\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^5-x^4+x^2-x+1\right)\)
g: \(4x^4+81\)
\(=\left(2x^2\right)^2+9^2\)
\(=\left(2x^2\right)^2+36x^2+9^2-36x^2\)
\(=\left(2x^2+9\right)^2-36x^2\)
\(=\left(2x^2+6x+9\right)\left(2x^2-6x+9\right)\)
h: \(64x^4+y^4\)
\(=64x^4+16x^2y^2+y^4-16x^2y^2\)
\(=\left(8x^2+y^2\right)^2-16x^2y^2\)
\(=\left(8x^2-4xy+y^2\right)\left(8x^2+4xy+y^2\right)\)